‘De Novo’ Brain AVMs—Hypotheses for Development and a Systematic Review of Reported Cases - Ioan Alexandru Florian; Lehel Beni; Vlad Moisoiu; Teodora Larisa Timis; Ioan Stefan Florian; Adrian Balașa; Ioana Berindan-Neagoe (Medicina, 2021)
Background and Objectives: Brain arteriovenous malformations AVMs have been consistently regarded as congenital malformations of the cerebral vasculature. However, recent case reports describing “de novo AVMs” have sparked a growing debate on the nature of these lesions. Materials and Methods: We have performed a systematic review of the literature concerning de novo AVMs utilizing the PubMed and Google Academic databases. Termes used in the search were “AVM,” “arteriovenous,” “de novo,” and “acquired,” in all possible combinations. Results: 53 articles including a total of 58 patients harboring allegedly acquired AVMs were identified by researching the literature. Of these, 32 were male (55.17%), and 25 were female (43.10%). Mean age at de novo AVM diagnosis was 27.833 years (standard deviation (SD) of 21.215 years and a 95% confidence interval (CI) of 22.3 to 33.3). Most de novo AVMs were managed via microsurgical resection (20 out of 58, 34.48%), followed by radiosurgery and conservative treatment for 11 patients (18.97%) each, endovascular embolization combined with resection for five patients (8.62%), and embolization alone for three (5.17%), the remaining eight cases (13.79%) having an unspecified therapy. Conclusions: Increasing evidence suggests that some of the AVMs discovered develop some time after birth. We are still a long way from finally elucidating their true nature, though there is reason to believe that they can also appear after birth. Thus, we reason that the de novo AVMs are the result of a ‘second hit’ of a variable type, such as a previous intracranial hemorrhage or vascular pathology. The congenital or acquired characteristic of AVMs may have a tremendous impact on prognosis, risk of hemorrhage, and short and long-term management.